Computational study of the activation mechanism of wild-type parkin and its clinically relevant mutant - Cinviz, Zeynep Nur; Şensoy, Özge (My University, 2025)
Parkinson's disease (PD) is the second most prevalent neurodegenerative disorder. It impairs the control of movement and balance. Parkin mutations worsen the symptoms in sporadic cases and cause the early onset of the disease. Therefore, recent efforts have focused on the rescue of defective parkin by engineered proteins or small-molecule activators to enhance parkin activation. These attempts require holistic understanding of the multistep activation mechanism and molecular effects of disease-associated mutations. Hereby, we provided a comprehensive analysis of the activation mechanism of parkin and a clinically relevant mutant, parkinS167N, using molecular dynamics simulations based on the following crystal structures: (1) parkin, (2) parkin/pUb (phosphorylated Ubiquitin), (3) pparkin/pUb, and (4) pparkin/pUb/UbcH7-Ub. Each of these represents an individual step in the activation process. We showed that the mutation impacted the dynamics of not only the RING0 domain, where it is localized, but also the RING2, Ubl, and IBR domains. We identified residues participating in the allosteric interaction network involved in parkin activation. Some of them are mutated in PD-associated parkin variants. The RING0 domain provides a binding interface with various proteins, so understanding problems associated with the mutation paves the way to the discovery of effective engineered proteins or small molecules that activate mutant parkin.
Keywords: Mitophagy; Molecular Dynamics; Parkin Mutation; Parkinson's Disease; RING0 Domain